The mistletoe countess [large type] - Basham, Pepper (Basham, Pepper, Freddie and Grace mystery, 2023)
"Mistletoe is beautiful and dangerous, much like the woman from Lord Frederick's Percy's past, so when he turns over a new leaf and arranges to marry for his estate, instead of his heart, he never expects the wrong bride to be the right choice. Gracelynn Ferguson never expected to take her elder sister's place as a Christmas bride, but when she's thrust into the choice, she will trust in her faithful novels and overactive imagination to help her not only win Frederick's heart but also to solve the murder mystery of Havensbrook Hall before the ghosts from Frederick's past ruin her fairytale future"--